Regional features of modern Russian science (on the example of the republic of Bashkortostan of the Russian Federation) - E. I. Akhmetova (Вестник университета, 2024)
The article analyzes the regional peculiarities of modern Russian science. In the course of the research the works devoted to the training and reproduction of scientific personnel, as well as to improving the quality and efficiency of scientific activity have been studied. The general trends in the scientific personnel formation system have been revealed, and the factors and indicators that influence science development in the regions identified. A comparative analysis of scientific personnel training in Russia and abroad has been carried out, the distinctive and similar characteristics identified. The data on domestic universities publication activity have been presented. In the Russian universities subject rating the Republic of Bashkortostan universities are mainly in the third ten, which indicates the need to strengthen scientific programs financing, increase salaries and improve working conditions for researchers. An important factor in science successful development in the region is creating attractive conditions for young scientists, who play a key role in science and innovations development, as their participation is considered a scientific progress driver. The author emphasizes the importance of strengthening the science development in Russian regions, which requires not only financial investments, but also systemic changes aimed at supporting researchers and creating favorable working conditions.